Assessment of serum and salivary ceruloplasmin level in patients with oral lichen planus - Abbas, Aws W; Zaidan, Taghreed F; Al-Barrak, Abduladheem Y (Journal of Baghdad College of Dentistry, 2014)
Background: Oxidative stress is a deleterious process that can be an important mediator of damage to cell structures and consequently various disease states. Exposure to free radicals from a variety of sources has led organisms to produce a series of defense mechanisms. The antioxidant ceruloplasmin is a copper-containing ferroxidase that can oxidize ferrous iron (Fe2+) to its nontoxic ferric (Fe3+) form. Ferrous iron (Fe2+) is extremely damaging because of its ability to generate toxic free radicals. Oral lichen planus (OLP) is a chronic inflammatory oral mucosal disease of unknown etiology. Previous studies reported that reactive oxygen species may be involved in the pathogenesis of lichen planus. The aim of this study was to estimate the role of oxidative stress in pathogenesis of OLP through the study of serum and saliva ceruloplasmin as a marker of antioxidant status. Methods: Forty eight patients with histologically confirmed OLP by oral pathologist were included in this study. The sample group was split up in to two groups according to the clinical presentation of the lesions, 21 patients with reticular formation and 27 patients with erosive form together with 32 healthy looking volunteers that were age-matched with the patients. Serum and saliva ceruloplasmin activity was determined by oxidation of P-Phenylenediamine to give a blue - violet color that measured spectrophotometricaly at 525 NM. Results: Statistically, there was a substantial increase in serum and saliva ceruloplasmin levels of OLP patients group as compared to controls (p0.05). The study showed that there was no statistically significant correlation between serum and saliva ceruloplasmin levels in OLP patients group (r=-0.029, p>0.05). Conclusion: Oxidative status play a role in the pathogenesis of oral lichen planus represented by increased serum and saliva ceruloplasmin levels.